A Bimodal Tuning Curve for Spatial Frequency Across Left and Right Human Orbital Frontal Cortex During Object Recognition. (10th January 2013) - Fintzi, Anat R.; Mahon, Bradford Z.
Abstract : Orbital frontal cortex (OFC) is known to play a role in object recognition by generating "first-pass" hypotheses about the identity of naturalistic images based on low spatial frequency (SF) information. These hypotheses are evaluated by more detailed (and slower) ventral visual pathway processes. While it has been suggested on theoretical grounds, it remains unknown whether OFC also receives postrecognition feedback about stimulus identity. We used a novel paradigm in the context of functional magnetic resonance imaging that permits the first few hundred milliseconds of object recognition to be spread out over 120 s. OFC shows a robust response to low and relatively high SFs, whereas ventral stream regions display unimodal response distributions shifted toward high SFs. These findings in OFC were modulated by hemisphere, with right OFC differentially responding to low SFs and left OFC differentially responding to high SFs. Psychophysical experiments confirmed that the same ranges of SFs preferred by ventral stream regions are critical for determining the accuracy and speed of object recognition. Our findings indicate that OFC accesses global form (low SF information, right OFC) and object identity (high SF information, left OFC), and suggest that OFC receives feedback about the accuracy of its initial hypothesis regarding stimulus identity.